Reforming Islamic Family Law in Indonesia through Syibhul Iddah for Husbands: State Policy and Penghulu Perspectives - Rahmad Setyawan; Doli Witro; Iffah Al Walidah; Iim Septiana; Muhamad Agus Soleh; Novia Nurfadila; Rismanuddin (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
The state policy regulating the concept of syibhul iddah for husbands as outlined in Circular Letter Number: P-005/DJ.III/HK.00.7/10/2021 has sparked debate among religious officials in Indonesia. This paper aims to discuss the chronology of the emergence of the concept of syibhul iddah for husbands and analyse the responses or perspectives of the heads of the Office of Religious Affairs (KUA) in Indonesia. In addition, it also discusses the relevance of the concept of syibhul iddah to the reform of Islamic family law in Indonesia. Methodologically, this research is a juridical-empirical research. Primary data was obtained through interviews with several religious leaders spread across various regions of Indonesia, while secondary data was obtained from reference materials such as scientific articles, scientific books, etc. The data analysis techniques used were data condensation, data presentation, and conclusion drawing. The results of the study show that the state policy through a circular letter regulating syibhul iddah is based on several reasons. First, the prevalence of covert polygamy in society, which can harm women’s rights. Second, as a legal measure to fill the legal vacuum regarding new marriages for husbands during their wives ‘iddah period. Third, as a legal measure to support the spirit of gender equality between men and women in carrying out responsibilities after divorce. However, in its application within the Office of Religious Affairs (KUA), the circular letter still causes differences of opinion among religious leaders in Indonesia. On the one hand, the majority of religious leaders are very responsive and supportive of the issuance of the circular letter. On the other hand, there are a small number of religious leaders who criticise the circular letter.